Stress testing of the development of Russian regions in the context of external economic restrictions - I. V. Danilova; A. V. Rezepin; N. V. Pravdina (Модернизация, инновация, развитие)
Purpose: is to develop the model for stress testing of the impact of external constraints of Russian regions in the context of foreign economic constraints 2022–2023.Methods: the research is based on the theory of economic dynamics, regional economy and spatial development, the concept of the BANI world; the methodological basis of the study is a scenario approach to the formation of the stress testing model and the algorithm for determining the expected impact based on the machine learning method – the artificial neural network.Results: the study of scientific publications on the research topic, analysis of shock events, post-shock consequences (2006–2022) made it possible to substantiate feasibility of testing and differentiating the response of Russian regions to external constraints, applying the criteria of “shock-resistant” development, classifying economic space and identifying the territory with “shock-resistant” and “non-shockresistant”reactions. The model of regions stress testing has been developed, industrial and sectoral (67.6% importance) and spatial (32.4%) stabilization factors have been identified, areas of vulnerability to the restrictions of 2022-2023 and industrial regions with the potential for “non-shock-resistant” type of reaction have been identified.Conclusions and Relevance: the reaction of regions to external economic shocks (the duration of the decline period and the intensity of recovery growth) is determined by the totality of the production and spatial characteristics of the regions. The results of the study are important for the development of the theory of regional economy; they can be used byfederal and regional executive authorities of the Russian Federation.